Peran Strategis Komunikasi Pemasaran dan Kualitas Produk dalam Membangun Loyalitas Pelanggan: Integrasi Perspektif Kepercayaan dan Nilai Pelanggan pada Ritel Modern Alfamart - Durosid, Durosid; Yudianto, Agus; Sonjaya, Nana Supriatna (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2026)
The purpose of this study is to examine how marketing communication and product quality affect Alfamart customers' loyalty. Alfamart must comprehend the elements that influence consumer loyalty in order to preserve and grow its market share in the face of growing competition in the retail industry. One hundred Alfamart clients in Indramayu were given a questionnaire as part of the research methodology. To test the hypothesis, several regression analysis approaches were applied to the acquired data. According to the study's findings, Alfamart's customer loyalty is positively but not significantly impacted by marketing communications. In the meantime, Alfamart's customer loyalty is positively and significantly impacted by pleanggan quality. These results show that high-quality products and efficient marketing communication techniques can raise customer satisfaction, which would eventually increase brand loyalty on Alfamart. In order to sustain consumer loyalty in the face of escalating competition, Alfamart is anticipated to benefit from this research by continuing to enhance its communication strategy and guarantee product quality.